PENGARUH KOMPETENSI GURU DAN DISIPLIN KERJA TERHADAP KINERJA GURU DI SMK NEGERI 14 MEDAN - Belqis Cecillia Tyara Wahyu; Bachruddin Saleh Luterlean (Institut Pendidikan Tapanuli Selatan, 2021)
In this globalization era teachers are required to be able to provide maximum contribution and goodperformances to achieve a goal. one of the factors that influence teacher’s performance is the competence of theteacher concerned both related to the teaching strategy, competencies, social and personal competencies as wellas competencies related to the profession being carried out. teacher performance is also determined by the highor low level of work discipline, those the school which in the teaching and learning process, growth discipline,will function as a form of individual values and norms, self control, attitude, and responsibilities for the teacherconcerned. The purpose of this study was to determine and analyze the Effect of Teacher’s Competence andWork Discipline on Teacher’s Performance.This research uses quantitative methods which are descriptive and causal research types. Samplingusing nonprobability sampling method type cluster sampling, the number of respondents was 69 people. Dataanalysis techniques used descriptive analysis and multiple linear regression analysis. The results of the study arebased on descriptive analysis of teacher’s competence, work discipline and teacher’s performance in eithercategory. The results of teacher’s competence multiple linear regression analysis and work disciplinesimultaneously have a significant effect on teacher’s performance. The magnitude of the influence of teacher’scompetence and work discipline store simultaneously affect teacher’s performance by 68,3%, the remaining31,7% is influenced by other variables not examined in this study. Partially teacher’s competence and workdiscipline have a significant effect on teacher’s pe